An improved valuation model for technology companies - Ako Doffou (International Journal of Financial Studies, 2015)
This paper estimates some of the parameters of the Schwartz and Moon (2001)) model using cross-sectional data. Stochastic costs, future financing, capital expenditures and depreciation are taken into account. Some special conditions are also set: the speed of adjustment parameters are equal; the implied half-life of the sales growth process is linked to analyst forecasts; and the risk-adjustment parameter is inferred from the company's observed stock price beta. The model is illustrated in the valuation of Google, Amazon, eBay, Facebook and Yahoo. The improved model is far superior to the Schwartz and Moon (2001) model.
Keywords: G12; 330; valuation; cross-sectional data; stochastic costs; speed of adjustment; implied half-life; risk-adjustment parameter